A conceptual investigation into brand mimicry in the luxury brand industry - Teah, Min; Phau, Ian (Recent Advances in Retailing and Services Science, 2010)
Copying, imitation, counterfeiting and knock-offs have been considered to be detrimental to the global economy and to innovation. While Mimicry has been applied to various areas of sciences such as engineering, biomimetics and behavioural sciences or even in areas of Management, it is however rarely applied in Marketing. Based on the Theory of Mimicry, the mimicry phenomenon that animals use in nature is a direct reflection of what is occurring in our marketplace, specifically the luxury brand industry. It can be observed that copying extends beyond direct counterfeiting and there are established and well known luxury brands who are participants of various degrees of brand mimicry – which is the copying of style, design or even product. The presence of mimicry can be applied to facets of the marketplace. It is of interest that the study examines whether mimicry inhibits innovation, or which type of mimicry would be better evaluated. As such, mimicry in Marketing is defined and various levels of mimicry reflected in our marketplace will be categorized according to the biological definitions. Real life marketing examples will serve as the stimulus through an experimental design. A conceptual model is developed which can be applied and test across various types of mimicry. The model also explores how the degree of mimicry would affect perception of luxury and consumer evaluations between the original and the mimic brand. Various theories from biology, sociology and psychology are used to explain the mimicry phenomenon. The implications of the study will contribute conceptually, methodologically and managerially.